Farm forestry in Karnataka and Tamil Nadu - an overview of Performance - Kareemulla, K.; Girijesh, G. K.; Sainath Kumar Rannorey, D. K.; Keshavaiah, K. V.; Koppalkar, B. G. (Indian Forester, 1994)
A field level Study was condueted in the States of Karnataka and Tamil Nadu in Farm Forestry projects. The main objective Was to make available local and individual need of wood and other produce. In block plantations, most of the produce was sold out while in bund/hedge planting the share of produce sold was relatively low in both the States.